2019
DOI: 10.1111/1750-3841.14824
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Pectinase‐Treated Prunus Mume Fruit Concentrate on Colorectal Cancer Proliferation and Angiogenesis of Endothelial Cells

Abstract: Pectinase is a well‐known enzyme used in the food processing industry to produce fruit juice and concentrate. This study evaluated the anticancer and antiangiogenesis activities of pectinase‐treated Prunus mume fruit concentrate (PC) and its phenolic components. PC treatment (250 to 1,000 µg/mL) resulted in decreased proliferation of SW480 human colorectal cancer cells through S‐phase cell cycle arrest; however, equivalent concentrations of PC did not show toxicity toward CRL‐1539 colon normal cells. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The antitumor effects of P. mume have been an important focus of pharmacological studies of the plant in recent years. MK615 and other compounds extracted from P. mume have exhibited anti-proliferative activity in vitro on many human cancer cell lines (Jeong et al, 2006), for example, the human hepatocellular carcinoma cell lines HuH7, HepG2, and Hep3B (Okada et al, 2007;Sakuraoka et al, 2010); human colon cancer cell lines SW480, COLO, and WiDr (Mori et al, 2007;Cho et al, 2019); human pancreatic cancer cell lines PANC-1, PK-1, PK45H, and MIAPaCa-2 cells (Toshie, 2008;Hattori et al, 2013); human malignant melanoma cell lines SK-MEL28 and A375 cells (Tada et al, 2012); human breast cancer cell lines MDA-MB-468 and MCF-7 cells (Nakagawa et al, 2007); human lung cancer cell lines A549 and PC14 cells (Sunage et al, 2011); and human leukemia cell lines HIMeg, HL-60, and Su9T01 cells (Shen et al, 1995;Kai et al, 2011). The proposed antitumor mechanisms, involved directly suppressing Aurora A and Aurora B kinase activity, inhibition of NF-κB activation (Toshie, 2008), triggering of apoptosis and autophagy (Mori et al, 2007), inducing accumulation of ROS in cancer cells but not in normal endothelial cells (Hattori et al, 2013), inhibition of the ERK1/2 and DNA binding-1 (Id-1) pathways, decreasing Bcl-2 expression (Tada et al, 2012), and suppressing hypoxia tolerance by up-regulation of E-cadherin in cancer cells with mutant KRAS (Nishi et al, 2020).…”
Section: Antitumor Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor effects of P. mume have been an important focus of pharmacological studies of the plant in recent years. MK615 and other compounds extracted from P. mume have exhibited anti-proliferative activity in vitro on many human cancer cell lines (Jeong et al, 2006), for example, the human hepatocellular carcinoma cell lines HuH7, HepG2, and Hep3B (Okada et al, 2007;Sakuraoka et al, 2010); human colon cancer cell lines SW480, COLO, and WiDr (Mori et al, 2007;Cho et al, 2019); human pancreatic cancer cell lines PANC-1, PK-1, PK45H, and MIAPaCa-2 cells (Toshie, 2008;Hattori et al, 2013); human malignant melanoma cell lines SK-MEL28 and A375 cells (Tada et al, 2012); human breast cancer cell lines MDA-MB-468 and MCF-7 cells (Nakagawa et al, 2007); human lung cancer cell lines A549 and PC14 cells (Sunage et al, 2011); and human leukemia cell lines HIMeg, HL-60, and Su9T01 cells (Shen et al, 1995;Kai et al, 2011). The proposed antitumor mechanisms, involved directly suppressing Aurora A and Aurora B kinase activity, inhibition of NF-κB activation (Toshie, 2008), triggering of apoptosis and autophagy (Mori et al, 2007), inducing accumulation of ROS in cancer cells but not in normal endothelial cells (Hattori et al, 2013), inhibition of the ERK1/2 and DNA binding-1 (Id-1) pathways, decreasing Bcl-2 expression (Tada et al, 2012), and suppressing hypoxia tolerance by up-regulation of E-cadherin in cancer cells with mutant KRAS (Nishi et al, 2020).…”
Section: Antitumor Effectsmentioning
confidence: 99%
“…To date, phytochemical studies have discovered numerous chemical components of the plant, mainly phenolics (Xia et al, 2011;Mitani et al, 2013), flavonoids (Yan et al, 2014a), and organic acids (Gao, 2012). Modern pharmacological studies have disclosed various biological activities and bioactive mechanisms of P. mume and its formulas, including antidiabetic (Kishida et al, 2013;Ko et al, 2013), hepatoprotective (Hokari, 2012;Beretta et al, 2016), antitumoral (Hattori et al, 2013;Cho et al, 2019), antiinflammatory (Morimoto et al, 2009;Mitani et al, 2013), and antimicrobial (Lee and Stein, 2011;Seneviratne et al, 2011) activities. Bailly (2020) reviewed anticancer properties of P. mume extracts, however, no comprehensive review on the phytochemical and pharmacological properties of P. mume is available.…”
Section: Introductionmentioning
confidence: 99%
“…The active compound 4-hydroxy-3,5-dimethoxybenzoic acid is derived from Euterpe oleracea and Rhus javanica extract, and inhibits colorectal cancer and oral squamous cell carcinoma [ 46 , 47 ]. Syringic acid (0.2 and 1 mM) prevented UVB (0.2 J/cm 2 )-induced skin papilloma and tumors in SKH-1 hairless mice [ 48 ].…”
Section: Akt and Related Signaling Pathway Inhibitors For Skin Canmentioning
confidence: 99%
“…Moreover, pectinases are applied for bioethanol production, liquefaction and saccharification of biomass, bio-scouring of cotton fiber, retting and degumming plant fiber, and oil extraction [3][4][5]. A recent study also showed that pectinase-treated fruit juice has inhibitory effects on colorectal cancer proliferation [6]. Due to the extensive applications of pectinase in different avenues, the demand for pectinase enzymes is increasing continuously [7].…”
Section: Introductionmentioning
confidence: 99%